The arms race in Asia trends, concepts and implications - Tan, Andrew T. H. (Andrew Tian Huat) (Asian Security Studies, 2014)
"This book is the first systematic examination of the emerging arms race in Asia.The global trade in arms is to a large degree underpinned by the strong demand for arms in Asia and the Middle East, the two largest arms export markets in the world. Of these two regions, Asia has become significant because the 21st century is shaping up to be the Asian century, led by the emergence of China and India as major powers. It is therefore not surprising that the phenomenon of rapid military modernization in Asia, accompanied by significant increases in the size and sophistication of armed forces, has generated attention as to its trends, key characteristics, causes and implications. This phenomenon, which has become evident since the end of the Cold War, has also been widely described as an Asian 'arms race'.This book seeks to: evaluate the key conceptual ideas which can shed light on the Asian arms race phenomenon; to explain in a systematic manner the evolving trends and the key characteristics of the Asian arms race; examine the multifaceted causes and underlying dynamics of the Asian arms race; evaluate the implications of the Asian arms race; and to assess the key issues arising from the Asian arms race.The book will be of great interest to students of Asian politics, strategic studies, defence studies, security studies and IR in general".